Network Analysis of Effect of Light-Dark Time Ratio on the Gene Expression Profile of Mouse Skin: Light-Dark Time Ratio and Gene Expression - Rezaei-Tavirani, Mostafa; Arjmand, Babak; Hamzeloo Moghadam, Maryam; Razzaghi, Zahra; Rostami-Nejad, Mohammad; Zamanian Azodi, Mona; Khodadoost, Mahmood; Rezaei-Tavirani, Majid; Ahmadzadeh, Alireza (Journal of Lasers in Medical Sciences, 2022)
Introduction: Circadian rhythms refer to daily cyclic events such as activity and rest in biology. A protein-based core related to the mechanism of circadian is identified. In the present study, the gene expression profiles of mouse skin in different conditions of light-dark times were investigated via protein-protein interaction (PPI) analysis to explore the main affected genes. Methods: GSE174155 was derived from Gene Expression Omnibus (GEO) and was analyzed via GEO2R to find the significant differentially expressed genes (DEGs). The gene expression profiles of Cry-null (genotype: cryptochrome-1(-/-): crytochrome-2 (-/-)) mouse skin versus the wild-type samples in the various circadian times (CTs) were assessed. The queried DEGs plus 50 first neighbors were included in a PPI network via the STRING database by Cytoscape software. The networks were analyzed and the central nodes were evaluated. Results: Three groups of mice based on CTs were identified. 15, 15, and 14 central nodes were determined as central nodes for the analysis networks. There was not a common central node for the analyzed networks. Conclusion: It was pointed out that the light/dark time ratio had a gross effect on the gene expression profile of the skin in the mice. Results imply more investigations to suggest a standard protocol related to CT, considering human lifestyle and exploring suitable protective methods for the jobs which are fixed in the abnormal CT sets.